1995
DOI: 10.1207/s15327558ijbm0204_3
|View full text |Cite
|
Sign up to set email alerts
|

Effects of racist provocation and social support on cardiovascular reactivity in african american women

Abstract: It has been speculated that exposure to the chronic stress of racism contributes to the high rates of hypertension among African Americans. Social support may buffer the effects of stress on cardiovascular (CV) health by attenuating stress-induced CV responses that have been linked to hypertension. In this study we investigated the effects of racism and social support on CV reactivity in African American women. Participants showed greater increases in CV and emotional responses while responding and listening t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
47
3

Year Published

2000
2000
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(52 citation statements)
references
References 52 publications
2
47
3
Order By: Relevance
“…Consistent with previous research (6), we did not find evidence that Blacks are generally more reactive to stressors than Whites, yet we did find that, relative to White women, Black women tended to get more aroused to a stressor that could be construed as racist than to a nonracial stressor. Previous studies (26)(27)(28) also have shown that racist stimuli can generate greater sympathetic arousal than nonracist stimuli among Black responders. However, because these previous studies lacked a comparison group of White participants, one cannot conclude from them that the differential reactivity to diverse social stressors is unique to Black responders.…”
Section: Discussionmentioning
confidence: 88%
“…Consistent with previous research (6), we did not find evidence that Blacks are generally more reactive to stressors than Whites, yet we did find that, relative to White women, Black women tended to get more aroused to a stressor that could be construed as racist than to a nonracial stressor. Previous studies (26)(27)(28) also have shown that racist stimuli can generate greater sympathetic arousal than nonracist stimuli among Black responders. However, because these previous studies lacked a comparison group of White participants, one cannot conclude from them that the differential reactivity to diverse social stressors is unique to Black responders.…”
Section: Discussionmentioning
confidence: 88%
“…Experiences of discrimination or unfair treatment may trigger a number of physiological responses related to stress or anger, as well as direct psychological experiences such as depression or anxiety (Mays et al 2007;McNeilly et al 1995;Clark et al 1999;Harrell et al 2003). Immediate physiologic responses to perceived racism have been demonstrated in laboratory settings (Clark et al 1999;Harrell et al 2003;Bennett et al 2004;Merritt et al 2006).…”
Section: Discrimination and Stressmentioning
confidence: 99%
“…To examine the extent to which African Americans would exhibit greater reactivity to racist stress, a debate procedure was used (see McNeilly et al, 1995). To manipulate racist stress, both African American and European American participants argued with a European American confederate about a race-related issue, such as racial differences in intelligence.…”
mentioning
confidence: 99%